Indonesia archipelago of fear - Vltchek, Andre (Pluto Press, 2012)
Indonesia: Archipelago of Fear is a fascinating and at times unsettling journey into the world's most populous Muslim nation as it struggles to emerge from decades of dictatorship and the plunder of its natural resources. Andre Vltchek brings together more than a decade of investigative journalism in and around Indonesia to chart the recent history of the country, from the revolution which overthrew General Suharto's genocidal dictatorship in 1998 to the present day. He covers the full breadth of the country from Islamic Aceh to mostly Catholic East Timor. Tracing Indonesia's current problems back to Suharto's coup and the genocide of 1965 - and the support given by the West to Suharto - Vltchek provides an intimate and deeply humane insight into the hopes and fears of Indonesia's people.